Head to Knee: Cranial Neural Crest-Derived Cells as Promising Candidates for Human Cartilage Repair - Ihsène Taïhi; Ali Nassif; Juliane Isaac; Benjamin Philippe Fournier; François Ferré (Hindawi Limited, 2019)
A large array of therapeutic procedures is available to treat cartilage disorders caused by trauma or inflammatory disease. Most are invasive and may result in treatment failure or development of osteoarthritis due to extensive cartilage damage from repeated surgery. Despite encouraging results of early cell therapy trials that used chondrocytes collected during arthroscopic surgery, these approaches have serious disadvantages, including morbidity associated with cell harvesting and low predictive clinical outcomes. To overcome these limitations, adult stem cells derived from bone marrow and subsequently from other tissues are now considered as preferred sources of cells for cartilage regeneration. Moreover, with new evidence showing that the choice of cell source is one of the most important factors for successful cell therapy, there is growing interest in neural crest-derived cells in both the research and clinical communities. Neural crest-derived cells such as nasal chondrocytes and oral stem cells that exhibit chondrocyte-like properties seem particularly promising in cartilage repair. Here, we review the types of cells currently available for cartilage cell therapy, including articular chondrocytes and various mesenchymal stem cells, and then highlight recent developments in the use of neural crest-derived chondrocytes and oral stem cells for repair of cartilage lesions.